A survey on the medical use of cannabis in Europe: a position paper - Bramness, Jørgen Gustav; Mann, Karl (European addiction research, 2018)
Aim: This study was aimed at investigating the availability and prescription of different medicinal variants of cannabis and their status in European countries. Methods: A web-based survey was sent to all member societies of the European Federation of Addiction Societies (EUFAS) in 2 waves during the summer of 2017. All 34 member societies in 19 different European countries were invited to participate. Results: We received 28 responses from 17 European countries. The cannabis extract nabiximol (Sativex®) is the most prevalent cannabis-based medicinal product marketed in Europe. Synthetic cannabinoids and standardized cannabis are less prevalent, and no country allows the growing of cannabis for personal medical use. The bringing of medical cannabis products from across borders to countries where the drug is not marketed is quite limited. The use of medical cannabis is restricted to some central medical conditions, but off-label use is prevalent in some countries. Conclusion: The use of medical cannabis in Europe seems to be restricted mostly to the use of the cannabis extract, nabiximol. There is only limited use of the cannabis plant as such for medical purposes, possibly indicating a different scenario in Europe as compared to the USA. Position Statement: EUFAS as an umbrella association of European addiction societies stresses the need for further studies on the efficacy of medical cannabis and warrants for possible dangers associated with the increasing popularity of medical cannabis. We need regulations at European level concerning registration and medical indications, development of uniform compounds and strength of products, and rules concerning sales and marketing.
Gesehen am 29.07.2019